Perfume slow-release agent under action of photocatalyst and preparation process of perfume slow-release agent
By combining the porous adsorption core and the encapsulation layer under the action of photocatalysts, using photocatalysts such as modified titanium dichloride and nanodiatom mud, the problem that existing fragrance sustained release agents cannot remove formaldehyde is solved, and the problem of existing fragrance sustained release agents is achieved. Effective adsorption and release of fragrances significantly improve air quality.
Patent Information
- Application Number
- CN202411676306.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-07
AI Technical Summary
Existing fragrance sustained-release agents cannot effectively remove harmful substances such as formaldehyde in the environment, resulting in limited air freshening effect.
The fragrance sustained release agent under the action of photocatalysts, consisting of porous adsorption cores (activated carbon, silicone, etc.) and encapsulation layer (agar, gelatin, etc.), combined with modified titanium dichloride, nanodiatom mud, nanosilver and other photocatalysts. The fragrance sustained release agent is formed through the preparation process to achieve adsorption and release of fragrances while removing formaldehyde from the air.
Effectively increase the adsorption capacity of spices, extend the release time of spices, significantly improve air quality, and reduce damage to the human body.
Smart Images

Figure CN119264986A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental optimization, and in particular to a fragrance sustained-release agent under the action of a photocatalyst and a preparation process thereof. Background Art
[0002] In recent years, it has become increasingly popular to use various devices to diffuse volatile compounds such as fragrances, disinfectants, insect repellents, etc. Currently, almost all households use air fresheners or deodorizers to mask bad odors or diffuse fragrance or other volatile active ingredients into the air around the device, especially in rooms and cabinets, garbage containers and other closed environments. Existing fragrance slow-release agents can only freshen the air but cannot remove harmful substances such as formaldehyde in the environment. Summary of the invention
[0003] Purpose of the invention: The purpose of the present invention is to provide a fragrance sustained-release agent under the action of photocatalysis and its preparation process; it can solve the problem that the existing fragrance sustained-release agent can only make the air fresh but cannot remove harmful substances such as formaldehyde in the environment.
[0004] Technical solution: To solve the above technical problems, according to one aspect of the present invention, more specifically, a flavor sustained-release agent under the action of photocatalyst, comprising the following components: one or more combinations of activated carbon, silica gel, polystyrene, poly(glycidyl methacrylate), one or more combinations of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, and an aqueous solution of galactomannan, one or more combinations of xylene, dichloroethane, petroleum ether, and heptane, one or more combinations of Span80, Span85, and Twen20, and a photocatalyst.
[0005] Furthermore, the fragrance sustained-release agent comprises the following components by weight: 30-70 parts of porous adsorption core, 20-50 parts of wrapping layer, 1-3 parts of additive one, 2-5 parts of additive two, and 5-10 parts of photocatalyst.
[0006] Furthermore, the photocatalyst includes the following components by weight: 60-80 parts of modified titanium dichloride, 6-8 parts of silicon dichloride, 15-35 parts of nano diatom mud, 3-9 parts of nano silver and 0.1-1.2 parts of flavor.
[0007] Furthermore, the flavor sustained-release agent includes a porous adsorption core and a coating layer; wherein the porous adsorption core is one or more combinations of activated carbon, silica gel, polystyrene, and poly(glycidyl methacrylate); the coating layer is composed of one or more combinations of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, and aqueous solutions of galactomannan, one or more combinations of xylene, dichloroethane, petroleum ether, and heptane, one or more combinations of Span80, Span85, and Twen20, and a photocatalyst.
[0008] According to another aspect of the present invention, the present invention provides a preparation process of a fragrance sustained-release agent under the action of a photocatalyst, and the process is implemented based on the components in the fragrance sustained-release agent under the action of a photocatalyst described above, and specifically comprises the following steps:
[0009] S1. Raw material preparation: preparing aqueous solutions of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, galactomannan and photocatalyst, and preparing one or more combinations of activated carbon, silica gel, polystyrene, poly(glycidyl methacrylate), one or more combinations of xylene, ethylene dichloride, petroleum ether, heptane, and one or more combinations of Span80, Span85, and Twen20;
[0010] S2, raw material mixing: stirring and mixing the prepared raw materials;
[0011] S3, solidification and washing: the raw materials after stirring and mixing are solidified into a spherical shape and then washed;
[0012] S4, forming the spheres and soaking them with spices;
[0013] S5. The unabsorbed fragrances are recovered and reused.
[0014] Furthermore, in S1, the preparation method of the aqueous solution of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, and galactomannan is: heating one or more combinations of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, and galactomannan with water in a ratio of 1:10-1:20 at 60°C for 1-2 hours; the preparation method of the photocatalyst is: mixing the prepared uniform and transparent nano silicon dichloride sol and the uniform and transparent nano titanium dichloride sol in a volume ratio of 1:10, stirring for 4.5-7h to obtain a uniform and transparent mixed sol, and then slowly adding nano diatom mud, nano silver and essence to the mixed sol in turn, and stirring and mixing for 2.5-5h.
[0015] Furthermore, in S2, the raw material mixing method is: stirring and mixing one or more combinations of activated carbon, silica gel, polystyrene, and poly(glycidyl methacrylate) with one or more combinations of an aqueous solution of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, and galactomannan; while stirring and mixing the activated carbon, silica gel, polystyrene, and poly(glycidyl methacrylate) with one or more combinations of an aqueous solution of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, and galactomannan, one or more combinations of xylene, dichloroethane, petroleum ether, heptane, one or more combinations of Span80, Span85, Twen20, and a photocatalyst are added dropwise during the stirring process.
[0016] Furthermore, in S3, the method of solidifying and molding the stirred and mixed raw materials is: pouring the stirred and mixed raw materials into a mold at 30° C. and solidifying them into a spherical shape.
[0017] Furthermore, in S4, the solidified spheres are immersed in the spices for 24 hours to 60 hours.
[0018] Furthermore, in the process of preparing the photocatalyst, the adsorption index of the nano-diatom mud can be obtained by obtaining the pore size and number of nano-diatom mud, the particle size and number of nano-silver, and the particle size and number of essence, and comprehensively analyzing the above data;
[0019]
[0020] Therefore, the direction of stirring time for adding nano-diatom mud, nano-silver and essence to the mixed sol can be determined according to the adsorption index of nano-diatom mud. The greater the adsorption index of nano-diatom mud, the shorter the stirring time can be selected, and vice versa, a longer stirring time can be selected, wherein XI is the adsorption index of nano-diatom mud, D1 is the pore size of nano-diatom mud, n1 is the number of nano-diatom mud, D2 is the particle size of nano-silver, n2 is the number of nano-silver, D3 is the particle size of essence, and n3 is the number of essence.
[0021] Beneficial effects: The fragrance sustained-release agent can effectively increase the adsorption of fragrances through one or more combinations of activated carbon, silica gel, polystyrene, and poly(glycidyl methacrylate) contained in the porous adsorption core, and at the same time, one or more combinations of aqueous solutions of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, etc., one or more combinations of xylene, dichloroethane, petroleum ether, heptane, one or more combinations of Span80, Span85, and Twen20 contained in the wrapping layer can effectively prolong the release time of the fragrance adsorbed in the porous core, and at the same time, the photocatalyst contained in the wrapping layer can effectively remove harmful components of formaldehyde in the air while improving the environmental odor, thereby improving the air quality of the environment and reducing harm to the human body. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the process flow;
[0023] Figure 2 It is a statistical table of indoor air conditions;
[0024] Figure 3 This is a real picture of this flavor sustained-release agent. DETAILED DESCRIPTION
[0025] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0026] Example 1
[0027] Heat agar and water at a ratio of 1:20 at 60°C for 1 hour, add 60 parts of modified titanium dichloride and 6 parts of silicon dichloride to prepare transparent titanium dichloride sol and transparent silicon dichloride sol, mix and stir for 4.5 hours to obtain a uniform and transparent mixed sol, then add 25 parts of nano diatom mud, 6 parts of nano silver and 0.5 parts of essence to the mixed sol in turn and stir and mix for 2.5 hours.
[0028] Then stir and mix 30 parts of activated carbon with the prepared agar water solution. During the stirring and mixing process, 1 part of xylene, 2 parts of Span80 and 5 parts of photocatalyst are added dropwise. The mixed raw materials are poured into a mold at 30°C to solidify into a sphere and then washed with water. Then, the solidified sphere is soaked with spices for 24 hours. Finally, the spices that are not adsorbed by the formed sphere are recovered and reused.
[0029] Example 2
[0030] Heat agar and water at a ratio of 1:15 at 60°C for 1.5 hours, add 70 parts of modified titanium dichloride and 7 parts of silicon dichloride to prepare transparent titanium dichloride sol and transparent silicon dichloride sol, mix and stir for 5.5 hours to obtain a uniform and transparent mixed sol, then add 15 parts of nano diatom mud, 3 parts of nano silver and 0.8 parts of essence to the mixed sol in turn and stir and mix for 3.5 hours.
[0031] Then, 50 parts of activated carbon were stirred and mixed with the prepared agar water solution. During the stirring and mixing process, 2 parts of xylene, 3 parts of Span80 and 7 parts of photocatalyst were added dropwise. The mixed raw materials were poured into a mold at 30°C and solidified into a sphere, which was then washed with water. The solidified sphere was then soaked with spices for 42 hours. Finally, the spices that were not adsorbed by the molded sphere were recovered and reused.
[0032] Example 3
[0033] Heat agar and water at a ratio of 1:10 at 60°C for 2 hours, add 80 parts of modified titanium dichloride and 8 parts of silicon dichloride to prepare transparent titanium dichloride sol and transparent silicon dichloride sol, mix and stir for 7 hours to obtain a uniform and transparent mixed sol, then add 35 parts of nano diatom mud, 9 parts of nano silver and 1.2 parts of essence to the mixed sol in turn and stir for 2.5 hours.
[0034] Then, 70 parts of activated carbon were stirred and mixed with the prepared agar water solution. During the stirring and mixing process, 3 parts of xylene, 5 parts of Span80 and 10 parts of photocatalyst were added dropwise. The mixed raw materials were poured into a mold at 30°C and solidified into a sphere, which was then washed with water. The solidified sphere was then soaked with spices for 60 hours. Finally, the spices that were not adsorbed by the molded sphere were recovered and reused.
[0035] Comparative Example 1
[0036] Agar and water were heated at 60°C in a ratio of 1:20 for 1 hour, and then 30 parts of activated carbon were stirred and mixed with the prepared agar water solution. During the stirring and mixing process, 1 part of xylene, 2 parts of Span80 and 5 parts of photocatalyst were added dropwise. The mixed raw materials were poured into a mold at 30°C and solidified into a sphere, followed by water washing. The solidified sphere was then soaked with spices for 24 hours. Finally, the spices not adsorbed by the formed sphere were recovered and reused.
[0037] Comparative Example 2
[0038] Agar and water were heated at 60°C for 1.5 hours at a ratio of 1:15, and then 50 parts of activated carbon were mixed with the prepared agar water solution. During the mixing process, 2 parts of xylene, 3 parts of Span80 and 7 parts of photocatalyst were added dropwise. The mixed raw materials were poured into a mold at 30°C to solidify into a sphere, and then washed with water. Then, the solidified sphere was soaked with spices for 42 hours, and finally the spices not adsorbed by the sphere were recycled and reused.
[0039] Comparative Example 3
[0040] Agar and water were heated at 60°C for 2 hours in a ratio of 1:10, and then 70 parts of activated carbon were stirred and mixed with the prepared agar water solution. During the stirring and mixing process, 3 parts of xylene, 5 parts of Span80 and 10 parts of photocatalyst were added dropwise. The mixed raw materials were poured into a mold at 30°C and solidified into a sphere, which was then washed with water. The solidified sphere was then soaked with spices for 60 hours. Finally, the spices not adsorbed by the formed sphere were recovered and reused.
[0041] Seven houses of the same type that were renovated at the same time and had just been completed were selected, and six of the houses were respectively placed with fragrance sustained-release agents made from the components of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, and the seventh house was not placed with any fragrance sustained-release agent, and the indoor air was measured 36 hours later.
[0042] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A fragrance sustained-release agent under the action of photocatalysis, characterized in that: The invention comprises the following components: one or more combinations of activated carbon, silica gel, polystyrene, poly(glycidyl methacrylate), one or more combinations of agar, gelatin, pectin, gum arabic, hemicellulose, aqueous solution of glucomannan, one or more combinations of xylene, ethylene dichloride, petroleum ether, heptane, one or more combinations of Span80, Span85, Twen20 and photocatalyst, and photocatalyst composition.
2. The fragrance sustained-release agent under the action of photocatalysis according to claim 1, characterized in that: The flavor sustained-release agent comprises the following components by weight: 30-70 parts of a porous adsorption core, 20-50 parts of a wrapping layer, 1-3 parts of an additive 1, 2-5 parts of an additive 2, and 5-10 parts of a photocatalyst.
3. The fragrance sustained-release agent under the action of photocatalysis according to claim 1, characterized in that: The photocatalyst comprises the following components by weight: 60-80 parts of modified titanium dichloride, 6-8 parts of silicon dichloride, 15-35 parts of nano diatom mud, 3-9 parts of nano silver and 0.1-1.2 parts of essence.
4. The fragrance sustained-release agent under the action of photocatalysis according to claim 1, characterized in that: The flavor sustained-release agent comprises a porous adsorption core and a coating layer; wherein the porous adsorption core is one or more combinations of activated carbon, silica gel, polystyrene, and poly(glycidyl methacrylate); the coating layer is composed of one or more combinations of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, and aqueous solutions of galactomannan, one or more combinations of xylene, dichloroethane, petroleum ether, and heptane, one or more combinations of Span80, Span85, and Twen20, and a photocatalyst.
5. A preparation process of a fragrance sustained-release agent under the action of photocatalysis, characterized in that: The method is implemented based on the component in the fragrance sustained-release agent under the action of photocatalysis as described in any one of claims 1 to 4, and comprises the following steps: S1. Raw material preparation: preparing aqueous solutions of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, galactomannan and photocatalyst, and preparing one or more combinations of activated carbon, silica gel, polystyrene, poly(glycidyl methacrylate), one or more combinations of xylene, ethylene dichloride, petroleum ether, heptane, and one or more combinations of Span80, Span85, and Twen20; S2, raw material mixing: stirring and mixing the prepared raw materials; S3, solidification and washing: the raw materials after stirring and mixing are solidified into a spherical shape and then washed; S4, forming the spheres and soaking them with spices; S5. The unabsorbed fragrances are recovered and reused.
6. The process for preparing a fragrance sustained-release agent under the action of photocatalysis according to claim 5, characterized in that: In S1, the preparation method of the aqueous solution of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate and galactomannan is: heating one or more combinations of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate and galactomannan with water at a ratio of 1:10-1:20 at 60°C for 1-2 hours; the preparation method of the photocatalyst is: mixing the prepared uniform and transparent nano silicon dichloride sol and the uniform and transparent nano titanium dichloride sol at a volume ratio of 1:10, stirring for 4.5-7h to obtain a uniform and transparent mixed sol, and then slowly adding nano diatom mud, nano silver and essence to the mixed sol in turn, and stirring and mixing for 2.5-5h.
7. The process for preparing a fragrance sustained-release agent under the action of photocatalysis according to claim 5, characterized in that: In S2, the raw material mixing method is: stirring and mixing one or more combinations of activated carbon, silica gel, polystyrene, and poly(glycidyl methacrylate) with one or more combinations of an aqueous solution of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, and galactomannan; during the stirring and mixing of activated carbon, silica gel, polystyrene, and poly(glycidyl methacrylate) with one or more combinations of an aqueous solution of agar, gelatin, pectin, gum arabic, hemicellulose, glucomannan, alginate, and galactomannan, one or more combinations of xylene, dichloroethane, petroleum ether, and heptane, one or more combinations of Span80, Span85, and Twen20, and a photocatalyst.
8. The process for preparing a fragrance sustained-release agent under the action of photocatalysis according to claim 5, characterized in that: In the above S3, the method of solidifying and molding the stirred and mixed raw materials is as follows: pouring the stirred and mixed raw materials into a mold at 30° C. and solidifying them into a spherical shape.
9. The process for preparing a fragrance sustained-release agent under the action of photocatalysis according to claim 5, characterized in that: In S4, the solidified spheres are immersed in the spices for 24 hours to 60 hours.
10. The process for preparing a fragrance sustained-release agent under the action of photocatalysis according to claim 6, characterized in that: In the process of preparing the photocatalyst, the adsorption index of the nano-diatom mud can be obtained by obtaining the pore size and number of nano-diatom mud, the particle size and number of nano-silver, and the particle size and number of essence, and comprehensively analyzing the above data; Therefore, the direction of stirring time for adding nano-diatom mud, nano-silver and essence to the mixed sol can be determined according to the adsorption index of nano-diatom mud. The greater the adsorption index of nano-diatom mud, the shorter the stirring time can be selected, and vice versa, a longer stirring time can be selected, wherein XI is the adsorption index of nano-diatom mud, D1 is the pore size of nano-diatom mud, n1 is the number of nano-diatom mud, D2 is the particle size of nano-silver, n2 is the number of nano-silver, D3 is the particle size of essence, and n3 is the number of essence.